Three essays on empirical finance - Hu, Xiaoxiong (Nanyang Technological University, 2022)
In essay one, I provide new evidence of the DRIP arbitrage activities based on Australian markets and investigate the impacts of DRIP arbitrage activities on equity lending, equity financing, and the price performance in the stock market. I find that DRIP arbitrage helps to facilitate equity raising through DRIPs with discount, and it increases search costs in the equity lending market and creates negative price pressure in the stock market over the DRIP pricing period. The financial markets are integrated in that the DRIP arbitrage activities fueled by the equity lending market could create temporary price pressure in the stock market, drain down the shares available for borrowing in the equity lending market, and facilitate fund raising in the equity financing market. In essay two, I investigate the impact of local political preference on green bond issuance and pricing outcomes based on the U.S. municipal bond market. I find that municipalities in Democratic leaning states and counties are more inclined to issue green municipal bonds than those in Republican leaning states and counties. There is not consistently significant “greenium” for green bonds issued in Democratic leaning states and counties, but there is significant pricing discount for green bonds issued in Republican leaning states and counties. In essay three, I examine how corporate bonds with green labels performed during the COVID-19 market crash using a matching method. I find that green bonds were subjected to higher selling-pressure than conventional bonds during the market sell-off period from 20 February to 23 March 2020. The findings contribute to the debate of whether investors’ preference towards green assets persists and injects resilience into asset prices during economic downturns, and echo the argument in Baumol and Oates (1988) that sustainability issues are “luxury goods” that are likely to be of concern when basic survival needs are adequately met.